EVALUATION OF IMAGE BLANC COMPLEXION LIGHTNER AND IMAGE BLANC SPOT LIGHTNER FOR HYPERPIGMENTATION IN FACE AND NECK - S, Arsiwala; S, Tahiliani; H, Jerajani; BS, Chandrashekhar; S, Aurangabadkar; M, Kohli; P, Savardekar; K, Sarangi; RD, Kharkar; F, Shah (Asian Journal of Pharmaceutical and Clinical Research, 2013)
Facial hyperpigmentation is a common, but challenging cosmetic condition to treat in skin of color. Image Blanc is a serum containing a core anti-ageing technology (Regen 16) that address all known major mechanisms involved in skin pigmentation. â€˜Image Blanc Complexion Lightner', is a corrective anti-ageing serum with complexion lightner actives & â€˜Image Blanc Spot Lightner', is an anti-spots concentrate for targeted application. An open labelled, prospective, multi-centric clinical study was conducted to determine the efficacy and safety of Image Blanc â€˜Complexion Lightner' and â€˜Spot Lightner' in the treatment of hyperpigmentation on face and neck twice daily for 12 weeks with 12 patients in each arm. The patients were assessed for Melasma Area and Severity Index (MASI) score for darkness, Physicians and Patient Global Assessment Grade for improvement in complexion or dark spots, improvement in â€˜Quality of Life', Patient Satisfaction Questionnaire and photographic assessment of the affected facial region at baseline, 6 weeks and 12 weeks. After 12 weeks of treatment by Image Blanc Complexion Lightner, the average MASI score at baseline was reduced to 1.4 from 2.4 at baseline, average grade for Physician's global assessment improved from 1 at baseline to 2.4Â andÂ with treatment of Image Blanc Spot Lightner it was reduced to 1.4 from 2.6 at baseline, average grade for Physician's global assessment improved from 1 at baseline to 2.8. Patient's global assessment also showed similar grades of improvement with Image Blanc Complexion Lightner and Image Blanc Spot Lightner. An overall improvement in â€˜Quality of Life' in terms of improvement in the complexion and luminance at the end of 12 weeks (Grade 3.3, 3.2) was noted by Image Blanc Complexion Lightner and Image Blanc Spot Lightner respectively. The overall â€˜Patient Satisfaction' was found to be good at the end of 12 weeks of treatment (Grade 2.6, 2.4) at the end of treatment with Image Blanc Complexion Lightner and Image Blanc Spot Lightner respectively. One patient on Image Blanc â€˜Spot Lightner showed acneform eruptions and darkening. The results of this study show that Image Blanc Complexion Lightner and Image Blanc Spot Lightner have a good potential for the management of hyperpigmentation disorders. Â Key Words: Hyperpigmentation, Image Blanc Complexion Lightner, Image Blanc Spot Lightner, Melasma Area and Severity Index (MASI) score